2017
DOI: 10.18632/oncotarget.15576
|View full text |Cite
|
Sign up to set email alerts
|

Activated Notch signaling augments cell growth in hepatocellular carcinoma via up-regulating the nuclear receptor NR4A2

Abstract: Hepatocellular carcinoma (HCC) is one of the most malignant cancers. Conventional therapies are limited due to the human liver being such a unique organ and easily showing side-effects. The unclear molecular mechanisms are tough challenges for scientists searching for new and effective anti-HCC targeting drugs. We identified that the nuclear receptor NR4A2 is a novel oncogene in HCC progression. In this study, we show that NR4A2 and the notch recceptor Notch1 were expressed highly in primary HCC tissues and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…mRNA levels showed that alteration of DEPDC1 expression significantly changed the expression of most of the selected genes in the SMCC‐7721 cells (Figure D), including NR4A2, SEPP1, EDN2, LYPD3, MMP9, WNT6, RAC2, WNT1, PTCH1 and CTNNB1. The oncogenic function of RAC2, NR4A2, MMP9 WNT1, PTCH1 and CTNNB1 has been reported in HCC . These results indicated that DEPDC1 may activate specific oncogenic signal pathways to promote HCC cell proliferation and metastasis.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…mRNA levels showed that alteration of DEPDC1 expression significantly changed the expression of most of the selected genes in the SMCC‐7721 cells (Figure D), including NR4A2, SEPP1, EDN2, LYPD3, MMP9, WNT6, RAC2, WNT1, PTCH1 and CTNNB1. The oncogenic function of RAC2, NR4A2, MMP9 WNT1, PTCH1 and CTNNB1 has been reported in HCC . These results indicated that DEPDC1 may activate specific oncogenic signal pathways to promote HCC cell proliferation and metastasis.…”
Section: Resultsmentioning
confidence: 75%
“…The oncogenic function of RAC2, NR4A2, MMP9 WNT1, PTCH1 and CTNNB1 has been reported in HCC. [17][18][19][20][21][22] These results indicated that DEPDC1 may activate specific oncogenic signal pathways to promote HCC cell proliferation and metastasis.…”
Section: Gene Set Enrichment Analysis Of Depdc1associated Signalingmentioning
confidence: 85%
“…Hepatocellular carcinoma (HCC) is considered as one of the most common malignancies and ranks third in cancerassociated deaths around the world. [1][2][3][4] About 250 000 new cases of HCC increase every year, with nearly 6 000 000 deaths occurring. 5 The conventional therapies at the early stages of HCC include surgical restriction, interventional therapy, radiotherapy and radiofrequency ablation.…”
Section: Introductionmentioning
confidence: 99%
“…3d, top) are strongly upregulated, together with the canonical NOTCH target gene HES1 35 and the liver specific target NR4A2 36 . These results are consistent with the proposed role of the NOTCH pathway in liver tumorigenesis 36,37 . Thus, we show that CMT transduced HFs undergo senescence, whereas the proliferative phenotype of CMT-iHep cells is associated with gene expression changes in Wnt and NOTCH signaling pathways.…”
Section: );mentioning
confidence: 99%